2021
DOI: 10.1002/adma.202100143
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Manipulation of Bulk Excitons and Surface Defects for Ultrastable and Highly Selective CO2 Photoreduction

Abstract: The objective of photocatalytic CO2 reduction (PCR) is to achieve high selectivity for a single energy‐bearing product with high efficiency and stability. The bulk configuration usually determines charge carrier kinetics, whereas surface atomic arrangement defines the PCR thermodynamic pathway. Concurrent engineering of bulk and surface structures is therefore crucial for achieving the goal of PCR. Herein, an ultrastable and highly selective PCR using homogeneously doped BiOCl nanosheets synthesized via an inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
120
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 209 publications
(126 citation statements)
references
References 56 publications
6
120
0
Order By: Relevance
“…The results of in situ FTIR spectra above have shown that the photoreduction of CO 2 to CO occurs through the COOH* and CO* on Ce ions of NaCeS 2 NCs, where the formation of COOH* is regarded to be the determining‐limiting step. [ 9,38,39 ] According to the calculated results shown in Figure a, the formation of COOH* intermediates over the NaCeS 2 NCs was endothermic and involved a large activation energy barrier (0.92 eV) (Tables S1 and S2, Supporting Information), thereby confirming that the CO 2 ‐to‐COOH* activation was the determining‐limiting step in the CO 2 photoreduction process. Next, the Gibbs free energy of CO* and CO were 0.36 and 0.56 eV, respectively, which means that absorbing 0.20 eV (∆E = ∆G CO − ∆G CO* ) was indispensable from the environment in CO desorption reaction (CO* → CO).…”
Section: Resultsmentioning
confidence: 85%
“…The results of in situ FTIR spectra above have shown that the photoreduction of CO 2 to CO occurs through the COOH* and CO* on Ce ions of NaCeS 2 NCs, where the formation of COOH* is regarded to be the determining‐limiting step. [ 9,38,39 ] According to the calculated results shown in Figure a, the formation of COOH* intermediates over the NaCeS 2 NCs was endothermic and involved a large activation energy barrier (0.92 eV) (Tables S1 and S2, Supporting Information), thereby confirming that the CO 2 ‐to‐COOH* activation was the determining‐limiting step in the CO 2 photoreduction process. Next, the Gibbs free energy of CO* and CO were 0.36 and 0.56 eV, respectively, which means that absorbing 0.20 eV (∆E = ∆G CO − ∆G CO* ) was indispensable from the environment in CO desorption reaction (CO* → CO).…”
Section: Resultsmentioning
confidence: 85%
“…[74,76,77] Impurity doping is one of the most commonly used strategies for enhancing photocatalysis performance, with the ability to extend the absorption range of the light spectrum, [78] modify band position, [79] enhance the stability of positive electric charge, and promote charge carrier excitation and separation. [80] Both nonmetals [81][82][83][84][85] and metals [86][87][88] can be used as dopant elements with slightly different mechanisms and effects. For example, metal doping can trap electrons and promote photoinduced electron-hole separation, [89] leading to enhanced redox ability.…”
Section: Defect Engineeringmentioning
confidence: 99%
“…This operando Raman spectroscopy results undoubtedly reveal that the O v in BiVO 4 can significantly promote water dissociation, and thus suppress the production of H 2 O 2 , consistent with the experimental results. Different from the prevalence of operando characterizations in other electrocatalytic fields like water splitting, [64][65][66][67] carbon dioxide reduction, [68][69][70] and nitrogen fixation, [71,72] the 2e-WOR related operando measurements is still in its infancy and much more efforts are desirable.…”
Section: Operando Investigations For Electrocatalytic 2e-wormentioning
confidence: 99%